Efficacy and safety of combination targeted therapies in immune-mediated inflammatory disease: the COMBIO study. Issue 1 (January 2023) - Guillo, Lucas; Flachaire, Benoit; Avouac, Jérôme; Dong, Catherine; Nachury, Maria; Bouguen, Guillaume; Buisson, Anthony; Caillo, Ludovic; Fumery, Mathurin; Gilletta, Cyrielle; Hébuterne, Xavier; Lafforgue, Pierre; et al.
Abstract: Background: Use of a combination of targeted therapies (COMBIO) in patients with refractory/overlapping immune-mediated inflammatory diseases (IMIDs) has increased, but reported data remain scarce. We aimed to assess effectiveness and safety of COMBIO in patients with IMIDs. Methods: We conducted a French ambispective multicenter cohort study from September 2020 to May 2021, including adults' patients with 1 or 2 IMIDs and treated at least 3-month with COMBIO. Results: Overall, 143 patients were included. The most common IMIDs were Crohn's disease (63.6%), axial spondyloarthritis (37.7%), and ulcerative colitis (14%). Half of patients had only one IMID, of which 60% were Crohn's disease. Mean duration of COMBIO was 274.5±59.3 weeks, and COMBIO persistence at 104 weeks was estimated at 64.1%. The most frequent COMBIOs combined anti-TNF agents with vedolizumab (30%) or ustekinumab (28.7%). Overall, 50% of patients achieved significant and 27% mild-to-moderate improvement in patient-reported outcomes. Extended duration of COMBIO (aOR=1.09; 95% CI: 1.03-1.14; p=0.002) and diagnoses of two IMIDs (aOR=3.46; 95%CI: 1.29-9.26; p=0.013) were associated with significant improvement in patient-reported outcomes. Incidence of serious infection during COMBIO was 4.51 per 100 person-years (95% CI 2.20-8.27) and 5 COMBIOs were discontinued due to adverse events. Conclusions: COMBIO can be effective and safe in patients with refractory/overlapping IMIDs.